Conceptual Notes on Sustainability and Corporate Social Responsibility in the Latin American Context - Chaihuaque Dueñas, Bruno (2019)
This article aims to contribute to the discussion on Corporate Social Responsibility from the Latin American context, which requires the inclusion of elements that are not adequately addressed in the American and European literature and whose relevance is lower compared to what happen in geographical areas of countries with a higher level of development. In that sense, some key elements are presented in the characterization of a particular context such as Latin American, as is the case of corruption, to understand the nature of the links between business and society, its effects and motivations. In the literature review, several concepts were found whose definition was ambiguous and which can cause theoretical inaccuracies that do not help the description of social phenomena. Likewise, the criterion for selecting the concepts has been that of instrumentalization; that is, highlight those concepts that facilitate the connection between elements of an ethical and economic nature. Finally, a typology was proposed to describe the links between business and society.